Stub Signature-Based Efficient Public Data Auditing System in Cloud Computing Using Holomorphic Algorithm - K. Sreenivasulu; Noortaj (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Online cloud statistics storage is a swiftly growing pillar of the IT industry that offers facts proprietors an array of attractive developments in fantastically sought-after online scalable garage offerings. Cloud customers can easily get admission to those offerings and feature the ability to control their procedure records effectively without disturbing about the deployment or preservation of private storage devices. As a end result, the range of cloud customers has increased to purchase those handy and value-effective services, while Cloud Service Providers also are growing to fulfil this call for attractive cloud solutions. However, there's one predominant security problem associated with outsourced data on shared cloud garage: its privacy and accuracy cannot be assured as it could be at risk of unauthorized get right of entry to via malicious insiders or hackers from out of doors resources. To deal with those problems, we advocate proposing a partial signature-primarily based facts auditing gadget so that both privacy and accuracy can be fortified whilst lowering the computational cost associated with auditing tactics drastically. This gadget could contain the use of cryptographic techniques including homomorphic encryption and hash functions, which could allow secure sharing among more than one parties while making sure integrity tests on saved files at normal intervals for any potential tampering attempts made by way of outside attackers or malicious insiders who may try to gain unauthorized get right of entry to into personal person facts saved inside cloud websites. Another benefit of the plan is that it supports dynamic operation on outsourced facts. This studies work may additionally gain the favoured protection traits, consistent with the security analysis, and its miles powerful for real-global packages, as verified by simulation outcomes of dynamic operations on various numbers of records blocks and sub-blocks.
Keywords: Homomorphic Encryption Algorithm; Cloud Computing; Data safety; Data Encryption; Data Decryption